Identification of compounds isolated from a methanolic extract of Acanthus ilicifolius leaves and evaluation of their antifungal and antioxidant activity - Dwi Andriani; SYAMSULINA REVIANTI; WIDYASRI PRANANINGRUM (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Andriani D, Revianti S, Prananingrum W. 2020. Identification of compounds isolated from a methanolic extract of Acanthus ilicifolius leaves and evaluation of their antifungal and antioxidant activity. Biodiversitas 21: 2521-2525. Acanthus ilicifolius L. (Acanthaceae) is commonly found in mangroves along the east coast of Surabaya. It can be used as an indicator of environmental pollution and damage in mangrove ecosystems. Studies have reported that A. ilicifolius has antimicrobial, antifungal, antiviral, anti-inflammatory, analgesic, antioxidant, anticancer, antileishmanial, and hepatoprotective activity due to the chemical compounds in the plant. This study aimed to determine the phytochemical compounds in methanolic extracts of A. ilicifolius and their antifungal and antioxidant activity. The study involved laboratory experiments with a post-test only control group design. Antifungal activity against Candida albicans biofilm was determined using microtiter plates. Antioxidant activity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Phytochemical screening used colorimetric methods. Methanolic extracts of A. ilicifolius at 16% and 20% concentration had the same inhibitory effect as nystatin against C. albicans (about 70% inhibition of biofilm). Chemical compounds identified in the extract included flavonoids, alkaloids, glycosides, polyphenols, tannins, and steroids. Methanolic extracts of A. ilicifolius have strong antioxidant and antifungal activity, and the plant’s phytochemical compounds are potential candidates for antifungal therapy.